Biodegradable resin composition, biodegradable film using the same, and method for preparing the same

By combining PLA and specific PHA resins and employing a biaxial stretching process, the problems of insufficient mechanical properties and transparency of PLA and PHA were solved, resulting in the preparation of a high-performance biodegradable film suitable for packaging materials.

CN120958082APending Publication Date: 2025-11-14MIKEVO GMBH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202480025666.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-14
Filing Date
2024-04-11
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing biodegradable polymers such as PLA and PHA are insufficient in terms of mechanical properties and transparency, making it difficult to meet the needs of packaging films, especially as they are prone to tearing and lack flexibility during stretching.

Method used

A biodegradable membrane is prepared by using a composition comprising PLA resin and a specific composition of PHA resin, wherein the PHA resin contains a mixture of repeating units containing 3-hydroxyhexanoic acid and 4-hydroxybutyric acid, through melt extrusion and biaxial stretching processes.

Benefits of technology

It improves the biodegradability, stretchability, and tensile strength of the membrane, while ensuring its transparency and flexibility, making it suitable for packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120958082A_ABST
    Figure CN120958082A_ABST
Patent Text Reader

Abstract

The present embodiment relates to a biodegradable resin composition, a biodegradable film using the same, and a method for preparing the same, wherein the biodegradable resin composition comprises: a polylactic acid (PLA) resin; and a polyhydroxyalkanoate (PHA) resin. The PHA resin includes: a first PHA resin including a 3-hydroxyhexanoate (3HH) repeating unit; and a second PHA resin comprising a 4-hydroxybutyrate (4HB) repeating unit, thereby simultaneously improving the biodegradability, stretchability, and strength of the biodegradable film. Therefore, the biodegradable resin composition according to an embodiment of the present invention has excellent biodegradability and biocompatibility, and thus is environmentally friendly, and can ensure sufficient stretchability and strength thereof to produce a stretchable film, thereby being used for producing various products requiring moldability, and also being suitable for the production of various products requiring moldability. The present invention relates to a packaging material, such as a packaging material for disposable bags or food containers, and exhibits excellent properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a biodegradable resin composition, a biodegradable film prepared using the biodegradable resin composition, and a method for preparing the biodegradable resin composition. Background Technology

[0002] With increasing public awareness of environmental issues in recent years, there is a need to address the disposal of various household products, especially disposable ones. Specifically, polymer materials are widely used in the manufacture of films, fibers, packaging materials, bottles, containers, and other products due to their low cost and excellent processability. However, their drawbacks are that incineration at the end of their lifespan releases harmful substances, while landfilling, depending on the type, can take hundreds of years to completely decompose naturally.

[0003] To overcome the limitations of these polymer materials, researchers are actively exploring environmentally friendly and rapidly degradable biodegradable polymers. While polylactic acid (PLA), polybutylene terephthalate (PBAT), polybutylene succinate (PBS), polybutylene terephthalate (PBST), and polybutylene adipate (PBSA) can be used as biodegradable polymers, their mechanical properties are inferior compared to non-degradable resins such as polyethylene terephthalate (PET), for example, they have lower crystallinity.

[0004] Specifically, PLA resin is a thermoplastic polymer obtained through the chemical synthesis of lactic acid produced by bio-fermentation. Its production process is environmentally friendly, and products made from it exhibit better biodegradability than those made from traditional polymer resins. However, PLA resin requires high temperatures to biodegrade and has relatively poor physical properties such as flexibility, which limits its applications in various fields.

[0005] Meanwhile, polyhydroxyalkanoate (PHA) resin is a biodegradable polymer that can be produced by various microorganisms, and it has attracted attention due to its excellent biodegradability and biocompatibility. Current research is underway to control the properties of PHA resin for its application in various fields.

[0006] Meanwhile, Korean Patent Publication No. 2014-0106880 discloses a biodegradable resin composition of polylactic acid (PLA) and polybutylene terephthalate (PBAT) with a controlled weight ratio, and a biodegradable mulch film using the composition. However, when blended with PBAT, PLA exhibits lower transparency and thermal properties, making it difficult to guarantee the required flexibility and strength for processing, which limits its applications. Summary of the Invention

[0007] Technical issues

[0008] Therefore, an object of one embodiment of the present invention is to provide a biodegradable resin composition having excellent biodegradability and mechanical properties (e.g., sufficient stretchability and strength) for use in the production of stretch films, biodegradable films using the same, and a method thereof.

[0009] Solution to the problem

[0010] According to one embodiment, a biodegradable resin composition is provided, comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

[0011] According to another embodiment, a biodegradable membrane prepared from a biodegradable resin composition is provided, wherein the biodegradable resin composition comprises polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, and wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

[0012] According to another embodiment, a method for preparing a biodegradable membrane is provided, the method comprising: preparing a biodegradable resin composition comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin; melt-extruding the biodegradable resin composition to prepare an unstretched sheet; first stretching the unstretched sheet in a first direction, and then second stretching the unstretched sheet in a second direction perpendicular to the first direction to prepare a stretched sheet; and heat-setting the stretched sheet at a temperature of 110°C to 160°C to prepare a biodegradable membrane, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

[0013] Advantages of the present invention

[0014] Since the biodegradable resin composition according to one embodiment comprises polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB), the biodegradability, stretchability and tensile strength of the biodegradable membrane can be enhanced.

[0015] Therefore, the biodegradable resin composition according to one embodiment is environmentally friendly because it possesses excellent biodegradability and biocompatibility, while ensuring sufficient stretchability and strength for the preparation of stretch films. Thus, it can be used to prepare packaging materials for a variety of products requiring formability, such as disposable bags and food containers, while exhibiting excellent performance.

[0016] Brief description of the attached figures

[0017] Figure 1 The tensile sheets of Examples 1 to 4 and Comparative Examples 1 to 3 according to Test Example 1 are shown.

[0018] Best mode for carrying out the invention

[0019] The present invention will now be described in detail with reference to the embodiments. However, the embodiments of the present invention are not limited to those described below. Rather, they can be modified in various forms without changing the spirit of the present invention.

[0020] Throughout this specification, when a part is referred to as "including" an element, it shall be understood to include other elements rather than exclude other elements, unless otherwise expressly stated.

[0021] In this specification, terms such as "first," "second," etc., are used to describe various components. However, the components should not be limited by these terms. These terms are only used to distinguish one component from another.

[0022] Unless otherwise stated, all figures used herein to represent the physical properties, dimensions, etc. of elements shall be understood to be modified by the term “about”.

[0023] Polylactic acid (PLA) resin, used as a biodegradable polymer, has an environmentally friendly production process, and products made from it exhibit better biodegradability than those made from traditional polymer resins. However, PLA resin suffers from low transparency and insufficient processing flexibility, making it difficult to apply in packaging film production. Specifically, due to its high crystallinity and low flexibility, PLA resin tears during stretching, making it unsuitable for film fabrication. Even when formed, the film tends to bend, resulting in poor appearance, low processability, and low productivity. Furthermore, PLA films are prone to cracking or breaking under impact at temperatures of 20°C or lower, and tend to become pasty at temperatures of 35°C or higher, thus making them unsuitable for packaging film manufacturing. Additionally, while PLA resin offers better biodegradability than traditional non-degradable resins, its commercialization has been hampered by the high temperatures required for biodegradation.

[0024] Meanwhile, polyhydroxyalkanoate (PHA) resin is a biodegradable polymer that can be produced by various microorganisms, and it has attracted attention due to its excellent biodegradability and biocompatibility. Since PHA resin is produced by microorganisms, it may contain many repeating units, and research is underway to control its properties by adjusting the type and content of these repeating units.

[0025] One embodiment of the present invention aims to optimize the biodegradability of a membrane while ensuring its mechanical properties, stretchability, etc., by using a biodegradable resin composition comprising PLA resin and PHA resin.

[0026] Specifically, the biodegradable resin composition according to one embodiment comprises polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB). Therefore, excellent biodegradability is achieved even at room temperature, while simultaneously enhancing stretchability and strength. In other words, the biodegradable resin composition according to one embodiment is environmentally friendly because it possesses excellent biodegradability and biocompatibility, while ensuring sufficient stretchability and strength for the preparation of stretch films.

[0027] More specifically, the biodegradable resin composition according to one embodiment comprises a specific PLA resin and a PHA resin suitable for said PLA resin, wherein said PHA resin comprises a first PHA resin containing 3HH repeating units and a second PHA resin containing 4HB repeating units. When a biodegradable film is manufactured using this material, transparency and flexibility are ensured, resulting in excellent appearance properties, while stretchability and processability are also ensured, preventing tearing even during stretching. Therefore, high-quality biodegradable films for packaging can be prepared.

[0028] Biodegradable resin composition

[0029] According to one embodiment, a biodegradable resin composition is provided, comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

[0030] According to one embodiment, the biodegradable resin composition comprises PLA resin.

[0031] Unlike petroleum-based resins, PLA resin is biomass-based, allowing the use of renewable resources. Compared to petroleum-based resins, it emits less carbon dioxide (a major cause of global warming) during production and is environmentally friendly because it is biodegraded by moisture and microorganisms when landfilled.

[0032] The PLA resin may contain repeating units derived from L-lactic acid (L-lactic acid repeating units), repeating units derived from D-lactic acid (D-lactic acid repeating units), repeating units derived from D,L-lactic acid (D,L-lactic acid repeating units), or combinations thereof.

[0033] Specifically, the PLA resin can be a random copolymer of L-lactic acid and D-lactic acid. In this case, based on the total number of moles of repeating units contained in the PLA resin, the content of L-lactic acid repeating units can be 80 mol% or more, 83 mol% or more, 85 mol% or more, 90 mol% or more, 93 mol% or more, 95 mol% or more, 98 mol% or more, or 99 mol% or more, and can be 80 mol% to 99.5 mol%, 83 mol% to 99 mol%, 85 mol% to 99 mol%, 90 mol% to 99 mol%, or 95 mol% to 99 mol%. When the content of L-lactic acid repeating units meets the above ranges, heat resistance can be enhanced.

[0034] Furthermore, based on the total number of moles of repeating units contained in the PLA resin, the content of D-lactic acid repeating units can be 1 mol% to 5 mol%, 1 mol% to 4 mol%, 2 mol% to 4 mol%, 1 mol% to 2 mol%, or 2 mol% to 3 mol%. When the content of D-lactic acid repeating units meets the above ranges, it may be advantageous from the perspective of enhancing the tensile processability of the film.

[0035] Furthermore, the weight-average molecular weight (Mw) of the PLA resin can be from 100,000 g / mol to 1,000,000 g / mol. Alternatively, the weight-average molecular weight of the PLA resin can be from 100,000 g / mol to 800,000 g / mol, 120,000 g / mol to 500,000 g / mol, or 150,000 g / mol to 300,000 g / mol. The weight-average molecular weight can be measured by gel permeation chromatography (GPC). When the weight-average molecular weight of the PLA resin meets the above ranges, the mechanical properties of the prepared membrane can be ensured, and the heat resistance of the membrane can be improved.

[0036] The glass transition temperature (Tg) of the PLA resin, measured by differential scanning calorimetry (DSC), can be from 30°C to 80°C, and the melting temperature (Tm) can be from 100°C to 250°C. For example, the glass transition temperature (Tg) of the PLA resin, measured by differential scanning calorimetry (DSC), can be from 35°C to 80°C, 40°C to 70°C, or 45°C to 65°C, and the melting temperature (Tm) can be from 105°C to 250°C, 110°C to 235°C, 120°C to 200°C, or 145°C to 185°C.

[0037] Differential scanning calorimetry (DSC) can be done with a Q2000 from TA Instruments. DSC measurements are performed in a nitrogen (N2) atmosphere.

[0038] Specifically, the first scan can be performed in differential scanning calorimetry (DSC) mode (1 st A second scan is performed, followed by a second scan, to obtain a heat flow profile for measuring the glass transition temperature (Tg), melting temperature (Tm), and crystallization temperature (Tc) of the PLA resin. More specifically, a heat flow profile can be obtained by heating from 40°C to 180°C at a rate of 10°C / min, cooling to -50°C at a rate of 10°C / min, and then heating from -50°C to 180°C at a rate of 10°C / min. During the second scan, Tg, Tc, and Tm are measured. In this case, the heat of crystallization can be calculated based on the integral of the crystallization temperature (Tc).

[0039] Furthermore, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 190°C and 2.13 kg) of the PLA resin can be from 2 g / 10 min to 5 g / 10 min. For example, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 190°C and 2.13 kg) of the PLA resin can be from 2.1 g / 10 min to 4.8 g / 10 min, 2.3 g / 10 min to 4.5 g / 10 min, 2.5 g / 10 min to 4.2 g / 10 min, or 2.6 g / 10 min to 4 g / 10 min.

[0040] According to one embodiment, the biodegradable resin composition may contain 10% by weight or more PLA resin. For example, based on the total weight of the biodegradable resin composition, the PLA resin content may be 12% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 35% by weight or more, 40% by weight or more, 50% by weight or more, 60% by weight or more, or 70% by weight or more, specifically, 10% to 70% by weight, 12% to 60% by weight, 15% to 55% by weight, 15% to 50% by weight, or 20% to 45% by weight. When the PLA resin content meets the above ranges, the mechanical properties of the membrane, such as tensile strength and flexibility, can be improved without reducing the optical properties of the membrane, such as transparency and light transmittance.

[0041] According to one embodiment, the biodegradable resin composition comprises PHA resin.

[0042] PHA resin is a natural thermoplastic polyester polymer that can accumulate within microbial cells. Depending on the type of repeating units (or monomers) that make up the PHA resin, its structure and physical properties can vary considerably.

[0043] Specifically, the PHA resin can be a copolymer polyhydroxyalkanoate (PHA) resin. More specifically, it can be a copolymer PHA resin with controlled crystallinity (crystallization).

[0044] For example, the PHA resin may contain at least one repeating unit derived from a monomer selected from the group consisting of: 3-hydroxybutyrate (3HB), 3-hydroxyhexanoate (3HH), 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), 3-hydroxypropionate (3HP), 5-hydroxyvalerate (5HV), 5-hydroxyhexanoate (5HH), and 6-hydroxyhexanoate (6HH). Specifically, the PHA resin may contain at least one repeating unit selected from the group consisting of: a repeating unit derived from 3-hydroxybutyrate (3HB) (3HB repeating unit), a repeating unit derived from 3-hydroxyhexanoate (3HH) (3HH repeating unit), and a repeating unit derived from 4-hydroxybutyrate (4HB) (4HB repeating unit).

[0045] According to one embodiment, the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoate (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyrate (4HB). Because the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoate (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyrate (4HB), it can enhance mechanical properties such as tensile strength and flexibility, as well as stretchability suitable for stretching processes.

[0046] The PHA resin can be a random copolymer containing 3HH repeating units and 3HB repeating units. For example, it can be PHBH (poly(3HB-co-3HH)) containing 3HH repeating units and 3HB repeating units.

[0047] The first PHA resin may contain 1 mol% to 10 mol% of 3HH repeating units. For example, the first PHA resin may be PHBH (poly(3HB-co-3HH)) containing 3HH repeating units, wherein the content of 3HH repeating units may be 1.5 mol% to 9 mol%, 2.5 mol% to 8.5 mol%, 4 mol% to 8 mol%, or 5.5 mol% to 7 mol% based on the total number of moles of repeating units contained in the first PHA resin.

[0048] The glass transition temperature (Tg) of the first PHA resin can be -5°C to 35°C, the melting temperature (Tm) can be 115°C to 160°C, and the crystallization temperature (Tc) can be 12°C to 30°C, as measured by differential scanning calorimetry (DSC). In this case, the heat of crystallization can be 10 J / g to 28 J / g.

[0049] For example, measured by differential scanning calorimetry (DSC), the glass transition temperature (Tg) of the first PHA resin can be -3°C to 25°C, -1°C to 10°C, or 0°C to 5°C; the melting temperature (Tm) can be 120°C to 155°C, 125°C to 150°C, or 135°C to 148°C; and the crystallization temperature (Tc) can be 13°C to 29°C, 15°C to 28°C, or 20°C to 27°C. In this case, the heat of crystallization can be 12 J / g to 27.5 J / g, 15 J / g to 27 J / g, 20 J / g to 27 J / g, or 24 J / g to 27 J / g.

[0050] Furthermore, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 165°C and 5 kg) of the first PHA resin can be from 5 g / 10 min to 25 g / 10 min. For example, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 165°C and 5 kg) of the PHA resin can be from 6 g / 10 min to 22 g / 10 min, 8 g / 10 min to 18 g / 10 min, 10 g / 10 min to 16 g / 10 min, or 11 g / 10 min to 14 g / 10 min.

[0051] The PHA resin may contain 20% to 70% by weight of a first PHA resin. For example, the content of the first PHA resin may be 22% to 65% by weight, 24% to 60% by weight, 25% to 55% by weight, or 26% to 48% by weight of the total weight of the PHA resin.

[0052] The second PHA resin can be an amorphous PHA resin (aPHA) with controlled crystallinity, and can be a random copolymer containing 4HB repeating units and 3HB repeating units. For example, it can be aPHA (poly(3HB-co-4HB)) containing 4-hydroxybutyrate (4HB) repeating units and 3-hydroxybutyrate (3HB) repeating units.

[0053] The second PHA resin may contain 15 mol% to 60 mol% of 4HB repeating units. For example, based on the total number of moles of repeating units contained in the second PHA resin, the third PHA resin may contain 20 mol% to 55 mol%, 25 mol% to 50 mol%, 28 mol% to 45 mol%, or 30 mol% to 40 mol% of 4HB repeating units. By ensuring the content of 4HB repeating units meets the above range, crystallinity can be easily controlled, thereby further improving stretchability and flexibility suitable for stretching processes. Furthermore, when a second PHA resin with a 4HB repeating unit content meeting the above range is further used, compatibility with PLA resin can be further enhanced.

[0054] Based on the total number of moles of repeating units contained in the second PHA resin, the content of 3HB repeating units in the second PHA resin can be 20 mol% or more, 25 mol% or more, 35 mol% or more, 50 mol% or more, 60 mol% or more, or 75 mol% or more.

[0055] The glass transition temperature (Tg) of the second PHA resin can be measured by differential scanning calorimetry (DSC) from -25°C to 0°C. For example, the glass transition temperature (Tg) of the second PHA resin can be measured by differential scanning calorimetry (DSC) from -20°C to -1°C, -15°C to -2°C, -20°C to -5°C, or -20°C to -10°C.

[0056] Furthermore, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 190°C and 2.16 kg) of the second PHA resin can be 5 g / 10 minutes or less. For example, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 190°C and 2.16 kg) of the second PHA resin can be 3.5 g / 10 minutes or less, 3 g / 10 minutes or less, 2.5 g / 10 minutes or less, or 2 g / 10 minutes or less.

[0057] The PHA resin may contain 60% by weight or less of a second PHA resin. For example, based on the total weight of the PHA resin, the content of the second PHA resin may be 50% by weight or less, 35% by weight or less, 25% by weight or less, or 20% by weight or less, specifically, 1% to 60% by weight, 2% to 50% by weight, 3% to 35% by weight, 5% to 30% by weight, 6% to 25% by weight, or 8% to 20% by weight. When the content of the second PHA resin meets the above ranges, transparency can be improved.

[0058] Meanwhile, the weight ratio of the first PHA resin to the second PHA resin can be from 95:5 to 5:95. For example, the weight ratio can be from 90:10 to 10:90, 90:10 to 50:50, or 85:15 to 60:40. When the weight ratio of the first PHA resin to the second PHA resin meets the above range, the crystallinity can be easily controlled. Therefore, the compatibility with PLA resin and the stretchability and flexibility suitable for stretching processes can be further enhanced, thereby improving the optical properties of the film.

[0059] According to one embodiment, the PHA resin may further comprise a third PHA resin containing repeating 3-hydroxyhexanoate (3HH) units. Specifically, the PHA resin may comprise all of the first to third PHA resins.

[0060] The third PHA resin can be a random copolymer containing 3HH repeating units and 3HB repeating units. For example, it can be PHBH (poly(3HB-co-3HH)) containing 3HH repeating units and 3HB repeating units. The third PHA resin and the first PHA resin can differ from each other in the content of 3HH repeating units.

[0061] Specifically, the third PHA resin may contain 10 mol% to 20 mol% of 3HH repeating units. For example, the third PHA resin may be PHBH (poly(3HB-co-3HH)) containing 3HH repeating units, wherein the content of 3HH repeating units may be 10 mol% to 18 mol%, 10.5 mol% to 15 mol%, or 11 mol% to 14 mol% based on the total number of moles of repeating units contained in the third PHA resin.

[0062] The molar ratio of the first PHA resin to the 3HH repeating unit of the third PHA resin can be from 1:0.5 to 5. For example, the molar ratio of the first PHA resin to the 3HH repeating unit of the third PHA resin can be from 1:0.6 to 4, 1:0.8 to 2.5, 1:1 to 2.3, or 1:1.2 to 2.

[0063] The glass transition temperature (Tg) of the third PHA resin can be -10°C to 10°C, the melting temperature (Tm) can be 145°C to 190°C, and the crystallization temperature (Tc) can be 35°C to 60°C, as measured by differential scanning calorimetry (DSC). In this case, the heat of crystallization can be 25 J / g to 50 J / g.

[0064] For example, measured by differential scanning calorimetry (DSC), the glass transition temperature (Tg) of the third PHA resin can be -8°C to 5°C, -5°C to 3°C, or -3°C to 0.5°C; the melting temperature (Tm) can be 150°C to 185°C, 152°C to 170°C, or 155°C to 168°C; and the crystallization temperature (Tc) can be 36°C to 55°C, 38°C to 52°C, or 40°C to 50°C. In this case, the heat of crystallization can be 26 J / g to 45 J / g, 27 J / g to 40 J / g, 28 J / g to 35 J / g, or 29 J / g to 32 J / g.

[0065] Furthermore, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 165°C and 5 kg) of the third PHA resin can be from 0.5 g / 10 min to 4.5 g / 10 min. For example, according to ISO 1133 and ASTM D1238, the melt flow index (MI, 165°C and 5 kg) of the third PHA resin can be from 0.6 g / 10 min to 4.2 g / 10 min, 0.8 g / 10 min to 4 g / 10 min, 1.2 g / 10 min to 3.8 g / 10 min, or 2 g / 10 min to 3.5 g / 10 min.

[0066] The PHA resin may contain 5% to 30% by weight of a third PHA resin. For example, the content of the third PHA resin may be 6% to 28% by weight, 8% to 25% by weight, 10% to 23% by weight, or 12% to 20% by weight of the total weight of the PHA resin.

[0067] Meanwhile, the weight ratio of the first PHA resin to the third PHA resin can be from 95:5 to 5:95. For example, the weight ratio of the first PHA resin to the third PHA resin can be from 90:10 to 10:90, 85:15 to 25:75, 80:20 to 35:65, 75:25 to 45:55, or 70:30 to 50:50. When the weight ratio of the first PHA resin to the third PHA resin meets the above ranges, sufficient stretchability and strength required for manufacturing the stretch film can be ensured simultaneously.

[0068] According to one embodiment, the biodegradable resin composition may contain 30% by weight or more of PHA resin. For example, based on the total weight of the biodegradable resin composition, the content of PHA resin may be 35% by weight or more, 45% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, or 80% by weight or more, specifically, 30% to 95% by weight, 35% to 92% by weight, 40% to 90% by weight, 45% to 88% by weight, 50% to 85% by weight, 60% to 80% by weight, or 62% to 75% by weight. When the content of PHA resin meets the above ranges, the mechanical properties of the membrane, such as tensile strength and flexibility, can be improved without reducing the optical properties of the membrane, such as transparency and light transmittance.

[0069] Furthermore, the weight ratio of the PLA resin to the PHA resin can be from 90:10 to 10:90. For example, the weight ratio of the PLA resin to the PHA resin can be 80:20 to 10:90, 70:30 to 10:90, 60:40 to 10:90, 55:45 to 15:85, 50:50 to 20:80, or 60:40 to 15:75. When the weight ratio of the PLA resin to the PHA resin meets the above ranges, mechanical properties, such as tensile strength and flexibility, can be further improved.

[0070] According to one embodiment, the biodegradable resin composition may also contain at least one additive selected from the group consisting of: ultraviolet stabilizers, heat stabilizers, antistatic agents, and dispersants.

[0071] The UV stabilizer may be at least one selected from the group consisting of benzophenones, benzotriazoles, cyanoacrylates, and salicylates, but is not limited thereto. Based on the total weight of the biodegradable resin composition, the content of the UV stabilizer may be from 0.5% to 2.5% by weight, 0.5% to 2.0% by weight, 1.0% to 2.0% by weight, or 1.5% to 2.0% by weight.

[0072] The heat stabilizer may be an iodine-based compound, but is not limited thereto. Based on the total weight of the biodegradable resin composition, the content of the heat stabilizer may be 0.01 wt% to 5 wt%, 0.05 wt% to 4 wt%, 0.1 wt% to 3 wt%, 0.15 wt% to 3 wt%, 0.3 wt% to 2.5 wt%, or 0.5 wt% to 2.5 wt%.

[0073] The antistatic agent may be at least one selected from the group consisting of quaternary ammonium salts, metal salts, conductive polymers, metal oxides, surfactants, and carbon nanotubes, but is not limited thereto. Based on the total weight of the biodegradable resin composition, the content of the antistatic agent may be from 0.01 wt% to 5 wt%, 0.05 wt% to 4 wt%, 0.1 wt% to 3 wt%, 0.15 wt% to 3 wt%, 0.3 wt% to 2.5 wt%, or 0.5 wt% to 2.5 wt%.

[0074] The dispersant may be at least one selected from the group consisting of polyacrylate compounds, polyurethane compounds, and polyester compounds, but is not limited thereto. Based on the total weight of the biodegradable resin composition, the content of the dispersant may be from 0.25% to 10% by weight, 0.3% to 7% by weight, 0.3% to 5% by weight, 0.5% to 3% by weight, 1% to 3% by weight, or 1.5% to 2.5% by weight.

[0075] Biodegradable membrane

[0076] According to another embodiment, a molding article prepared from the biodegradable resin composition is provided.

[0077] Specifically, the molded article can be prepared by molding the biodegradable resin composition by methods known in the art, such as extrusion or injection molding. The molded article can be an injection molded article, an extrusion molded article, a film molded article, or a blow molded article, but is not limited thereto.

[0078] In addition, the molded product can also be in the form of a film or sheet, which can be used as agricultural covering film, disposable gloves or food packaging material; it can also be in the form of fiber, which can be used as cloth, knitted fabric, non-woven fabric, rope; or it can be in the form of a container, which can be used as a food packaging container such as a lunch box.

[0079] Because the molded articles are made from a biodegradable resin composition with excellent biodegradability and biocompatibility, as well as excellent strength and processability, they exhibit excellent performance when used in packaging products.

[0080] Specifically, molded articles prepared from the biodegradable resin composition can be used as environmentally friendly packaging materials. For example, the environmentally friendly packaging material can be in the form of a film or sheet, which can be used as a common disposable film or food packaging material; it can also be in the form of fibers, which can be used as cloth, knitted fabric, non-woven fabric, rope; or it can be in the form of a container, which can be used as a food packaging container such as a lunch box.

[0081] For example, a biodegradable molded article may be composed of, or may contain, a biodegradable film prepared from a biodegradable resin composition.

[0082] According to another embodiment, the biodegradable membrane is prepared from a biodegradable resin composition comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

[0083] Details regarding the biodegradable resin composition, PLA resin, and PHA resin are as described above.

[0084] The elongation of biodegradable membranes can reach 300% or more. For example, the maximum deformation of a biodegradable membrane before breakage is measured using an INSTRON universal testing machine (model name: 4206) at a tensile speed of 200 mm / min and a temperature of 60°C. The ratio of the maximum deformation to the initial length is calculated as the elongation. In this case, the elongation in the longitudinal direction can be 320% or more, 350% or more, 360% or more, or 400% or more.

[0085] The tensile strength of the biodegradable membrane can be 10 kgf / mm. 2 Or less. For example, the biodegradable membrane is tested using an INSTRON universal testing machine (model: 4206) at a tensile speed of 200 mm / min and a temperature of 60°C, and the tensile strength is measured using the program installed in the equipment. In this case, the tensile strength might be 9 kgf / mm². 2 Or less, or 8 kgf / mm 2 Or less.

[0086] According to ISO 14855, the biodegradable membrane can have a biodegradability of 40% or higher under conditions of 28°C and 50% RH. For example, according to ISO 14855, the biodegradability of the biodegradable membrane can be 42% or higher, 45% or higher, 50% or higher, 65% or higher, 70% or higher, 75% or higher, 80% or higher, or 90% or higher, calculated based on the weight loss rate after 120 days at 28°C and 50% RH.

[0087] According to ASTM D6691, the biodegradable membrane can achieve a biodegradability of over 20% in seawater at 30°C. For example, based on the weight loss rate measured after 198 days in seawater at 30°C according to ASTM D6691, the biodegradability of the biodegradable membrane can be 25% or higher, 30% or higher, 33% or higher, 35% or higher, 38% or higher, 40% or higher, 45% or higher, 50% or higher, or 60% or higher.

[0088] The thickness of the biodegradable membrane can be from 5 μm to 200 μm. For example, the thickness of the biodegradable membrane can be from 5 μm to 180 μm, 5 μm to 160 μm, 10 μm to 150 μm, or 15 μm to 130 μm.

[0089] Methods for preparing biodegradable membranes

[0090] According to another embodiment, a method for preparing a biodegradable membrane is provided, the method comprising: preparing a biodegradable resin composition comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin; melt-extruding the biodegradable resin composition to prepare an unstretched sheet; first stretching the unstretched sheet along a first direction, and then second stretching the unstretched sheet along a second direction perpendicular to the first direction to prepare a stretched sheet; and heat-setting the stretched sheet at a temperature of 110°C to 160°C to prepare a biodegradable membrane. Here, the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoate (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyrate (4HB).

[0091] Details of the PLA resin and PHA resin are as described above.

[0092] The biodegradable resin composition can be prepared by mixing the PLA resin and PHA resin.

[0093] Subsequently, the biodegradable resin composition is melt-extruded at 170°C to 210°C to prepare an unstretched sheet. For example, the melt extrusion temperature can be 175°C to 210°C, or 175°C to 200°C.

[0094] Subsequently, the unstretched sheet is stretched for the first time along the first direction, and then stretched for the second time in a second direction perpendicular to the first direction to prepare a stretched sheet.

[0095] The first stretching can be performed at a temperature of 60°C to 120°C with a stretching ratio of 2 to 4 times. For example, the first stretching can be performed at a temperature of 70°C to 110°C, 75°C to 105°C, or 80°C to 100°C, with a stretching ratio of 2.2 to 4 times, 2.5 to 3.8 times, or 2.5 to 3.5 times. By ensuring that the temperature and stretching ratio of the first stretching meet the above ranges, stretchability can be improved.

[0096] The first direction can be either transverse (TD) or longitudinal (MD). Specifically, the first direction can be longitudinal (MD), and the second direction perpendicular to the first direction can be transverse (TD).

[0097] After the first stretching, a second stretching is performed along a second direction perpendicular to the first direction. For example, the second stretching can be performed at a temperature of 70°C to 140°C with a stretching ratio of 3 to 5 times. Alternatively, the second stretching can be performed at temperatures of 70°C to 135°C, 72°C to 110°C, or 75°C to 100°C, with a stretching ratio of 3.1 to 5 times, 3.2 to 4.8 times, or 3.3 to 4.8 times. By ensuring that the temperature and stretching ratio of the second stretching meet the above ranges, stretchability can be improved.

[0098] The ratio (d1 / d2) of the stretch ratio in the first direction (d1) to the stretch ratio in the second direction (d2) can be from 0.5 to 1. For example, the ratio (d1 / d2) of the stretch ratio in the first direction (d1) to the stretch ratio in the second direction (d2) can be from 0.5 to 0.95, from 0.65 to 0.95, or from 0.7 to 0.9.

[0099] Additionally, a preheating or coating step can be performed before the second stretching.

[0100] The preheating step can be performed at 70°C to 120°C for 0.01 minutes to 1 minute. For example, the preheating temperature can be 70°C to 120°C, 75°C to 115°C, or 80°C to 110°C, and the preheating time can be 0.01 minutes to 1 minute, 0.05 minutes to 0.5 minutes, or 0.08 minutes to 0.2 minutes.

[0101] The coating step may be a step that imparts functionality (e.g., antistatic properties) to the biodegradable membrane, and may be performed by spin coating or in-line coating, but is not limited thereto.

[0102] Finally, the stretched sheet is heat-set at 110°C to 160°C to prepare a biodegradable film. For example, the heat setting can be annealing, and can be performed at 125°C to 160°C, 130°C to 158°C, or 145°C to 155°C for 1 second to 5 minutes or 1 second to 3 minutes. After the heat setting is completed, a process of gradually decreasing the temperature can be performed.

[0103] This invention mode

[0104] The embodiments of the present invention will now be described in detail with reference to the specific implementation methods. However, these embodiments are for illustrative purposes only, and the embodiments of the present invention are not limited thereto. Example

[0105] Preparation of biodegradable membranes

[0106] Example 1

[0107] (1) Preparation of biodegradable resin composition

[0108] A polyhydroxyalkanoate (PHA) resin is prepared by mixing a first PHA resin and a second PHA resin at a weight ratio of 3:1. A biodegradable resin composition is prepared by mixing PLA resin and the PHA resin at a weight ratio of 40:60. In this case, the content of each resin in the biodegradable resin composition is as follows: PLA resin 40% by weight, first PHA resin 45% by weight, and second PHA resin 15% by weight.

[0109] PLA resin: a random copolymer of L-lactic acid and D-lactic acid, wherein the content of L-lactic acid repeating units is 98 mol%, the weight average molecular weight is 190,000 g / mol, the glass transition temperature (Tg) is 58 °C, the melting temperature (Tm) is 163.9 °C, and the melt flow index (MI, 190 °C and 2.16 kg) is 3.5 g / 10 min (according to ISO 1133 and ASTM D1238).

[0110] - First PHA resin: PHBH containing 3HH repeating units and 3HB repeating units, wherein the content of 3HH repeating units is 6.53 mol%, glass transition temperature (Tg) is 1℃, melting temperature (Tm) is 145℃, crystallization temperature (Tc) is 26.5℃, heat of crystallization is 26.6 J / g, and melt flow index (MI, 165℃ and 5kg) is 12 g / 10 min (according to ISO 1133 and ASTM D1238).

[0111] - Second PHA resin: PHA containing 3HB repeating units and 4HB repeating units, wherein the content of 4HB repeating units is 33 mol%, the glass transition temperature (Tg) is -20°C to -10°C, and the melt flow index (MI, 190°C and 2.16 kg) is 2 g / 10 min (according to ISO 1133 and ASTM D1238).

[0112] (2) Preparation of biodegradable membranes

[0113] The biodegradable resin composition prepared in Example 1 was fed into an extruder and melt-extruded at 190°C through a T-die. The extruded material was then cooled by a casting roller at 20°C to prepare an unstretched sheet. The unstretched sheet was then cut into 9cm wide and 9cm long pieces and stretched using a biaxial stretching machine at 80°C. First, the sheet was stretched at 3 times its original length in the MD direction, and then at 4 times its original length in the TD direction, to prepare a stretched sheet. The stretched sheet was then heat-set at 150°C for 10 seconds to prepare a biodegradable film.

[0114] Examples 2 to 4 and Comparative Examples 1 to 3

[0115] The biodegradable resin composition and biodegradable membrane were prepared in basically the same manner as in Example 1, except that the components and their contents were changed, as shown in Table 1 below.

[0116] - Third PHA resin: PHBH containing 3HH repeating units and 3HB repeating units, wherein the content of 3HH repeating units is 11.55 mol%, glass transition temperature (Tg) is -1℃, melting temperature (Tm) is 163℃, crystallization temperature (Tc) is 45℃, heat of crystallization is 30 J / g, and melt flow index (MI, 165℃ and 5kg) is 3 g / 10 min (according to ISO 1133 and ASTM D1238).

[0117] Table 1

[0118]

[0119] Test Example 1: Stretchability

[0120] The unstretched sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were stretched three times along the MD direction at 70°C. The central portion of each uniaxially stretched sheet was then cut into samples with a width of 1.5 cm and a length of 20 cm. Thickness was measured at every 20 points in each sample, and the difference between the maximum and minimum thickness was calculated to evaluate tensile properties based on thickness uniformity. Furthermore, the degree of shrinkage and the presence of wrinkles or other abnormalities on the surface were determined by visual inspection of each sample.

[0121] Table 2

[0122]

[0123] As can be seen from Table 2 above, Examples 1 to 4 exhibit excellent stretchability because the difference between the maximum and minimum thickness of each stretched sheet is small. Conversely, the differences between the maximum and minimum thickness of the stretched sheets in Comparative Examples 1 and 2, which did not use the second PHA resin, are greater than those in Examples 1 to 4. In Comparative Example 3, although all of the first to third PHAs were used, the PLA:PHA weight ratio and / or the weight ratio of the first PHA resin to the second PHA resin did not meet the desired range. Therefore, the difference between the maximum and minimum thickness of the stretched sheet was very large, resulting in low stretchability.

[0124] Figure 1 Tensile sheets of Examples 1 to 4 and Comparative Examples 1 to 3, according to Test Example 1, are shown. From Figure 1 It can be seen that the shrinkage and surface bending of Examples 1 to 4 are relatively small. Compared with Examples 1 to 4, Comparative Examples 1 and 2 exhibit deformations such as surface bending. In Comparative Example 3, surface bending and shrinkage are significant.

[0125] Example 5

[0126] The biodegradable membrane was prepared in the same manner as in Example 2, except that in step (2), the membrane was stretched only once along the MD direction at 80°C, with a stretching factor of 3.4 times.

[0127] Examples 6 and 7 and Comparative Examples 4 and 8

[0128] The biodegradable resin composition and biodegradable membrane were prepared in basically the same manner as in Example 5, except that the components and their contents were changed, as shown in Table 3 below.

[0129] Table 3

[0130]

[0131] Test Example 2: Biodegradability in Marine Environment

[0132] The biodegradability of the stretched sheets prepared in Examples 5 to 7 and Comparative Examples 4 to 8 was measured according to ASTM D6691. Specifically, each stretched sheet was immersed in seawater at 30°C, and its weight and thickness were measured for 198 days. The thickness difference and weight loss rate were calculated.

[0133] The thickness and weight loss rates of Examples 5 to 7 before and after 198 days are shown in Table 4 below. Comparative Examples 7 and 8 showed no change in thickness and weight before and after 198 days.

[0134] Table 4

[0135]

[0136] As can be seen from Table 4 above, compared with Comparative Examples 4 to 6 which did not use the second PHA resin, Examples 5 to 7 showed excellent biodegradability in the marine environment.

Claims

1. A biodegradable resin composition comprising polylactic acid (PLA) resin; and polyhydroxyalkanoate (PHA) resin, wherein the PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoic acid (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyric acid (4HB).

2. The biodegradable resin composition of claim 1, wherein the first PHA resin comprises 1 mol% to 10 mol% of 3HH repeating units, and the second PHA resin comprises 15 mol% to 60 mol% of 4HB repeating units.

3. The biodegradable resin composition of claim 1, wherein the weight ratio of the first PHA resin to the second PHA resin is 95:5 to 5:

95.

4. The biodegradable resin composition of claim 1, wherein the first PHA resin has a glass transition temperature (Tg) of -5°C to 35°C, a melting temperature (Tm) of 115°C to 160°C, a crystallization temperature (Tc) of 12°C to 30°C, and a heat of crystallization of 10 J / g to 28 J / g, as measured by differential scanning calorimetry (DSC), and a melt flow index (MI, 165°C and 5 kg) of 5 g / 10 min to 25 g / 10 min according to ISO 1133 and ASTM D1238.

5. The biodegradable resin composition of claim 1, wherein the second PHA resin has a glass transition temperature (Tg) of -25°C to 0°C as measured by differential scanning calorimetry (DSC), and a melt flow index (MI, 190°C and 2.16 kg) of 5 g / 10 min or less according to ISO 1133 and ASTM D1238.

6. The biodegradable resin composition of claim 1, wherein the PHA resin further comprises a third PHA resin containing a repeating 3-hydroxyhexanoate (3HH) unit, and The first PHA resin and the third PHA resin differ from each other in the content of 3HH repeating units.

7. The biodegradable resin composition of claim 6, wherein the third PHA resin comprises 10 mol% to 20 mol% of 3HH repeating units.

8. The biodegradable resin composition of claim 6, wherein the molar ratio of the 3HH repeating units of the first PHA resin to the third PHA resin is 1:0.5 to 5.

9. The biodegradable resin composition of claim 6, wherein the third PHA resin has a glass transition temperature (Tg) of -10°C to 10°C, a melting temperature (Tm) of 145°C to 190°C, a crystallization temperature (Tc) of 35°C to 60°C, and a heat of crystallization of 25 J / g to 50 J / g, as measured by differential scanning calorimetry (DSC), and a melt flow index (MI, 165°C and 5 kg) of 0.5 g / 10 min to 4.5 g / 10 min according to ISO 1133 and ASTM D1238.

10. The biodegradable resin composition of claim 6, wherein the PHA resin comprises 5% to 30% by weight of the third PHA resin.

11. The biodegradable resin composition of claim 1, wherein the PLA resin is a random copolymer of L-lactic acid and D-lactic acid, and the content of L-lactic acid repeating units therein is 80 mol% or more, and the weight-average molecular weight (Mw) is from 100,000 g / mol to 1,000,000 g / mol. The glass transition temperature (Tg) of the PLA resin, measured by differential scanning calorimetry (DSC), is 100°C to 250°C, and the melting temperature (Tm) is 100°C to 250°C. According to ISO 1133 and ASTM D1238, the melt flow index (MI, 190°C and 2.13 kg) of the resin is 2 g / 10 min to 5 g / 10 min.

12. The biodegradable resin composition of claim 1, wherein the weight ratio of the PLA resin to the PHA resin is 90:10 to 10:

90.

13. A biodegradable membrane prepared from a biodegradable resin composition, wherein the biodegradable resin composition comprises polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin, and The PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoate (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyrate (4HB).

14. The biodegradable membrane of claim 13, wherein the elongation of the biodegradable membrane is 300% or more and the tensile strength is 10 kgf / mm². 2 Or less, according to ISO 14855, the biodegradability is 40% or more at 28°C and 50% RH, and according to ASTM D6691, the biodegradability is 20% or more in seawater at 30°C.

15. A method for preparing a biodegradable membrane, comprising: Prepare a biodegradable resin composition comprising polylactic acid (PLA) resin and polyhydroxyalkanoate (PHA) resin; The biodegradable resin composition is melt-extruded to prepare an unstretched sheet; An unstretched sheet is first stretched along a first direction, and then a stretched sheet is second stretched along a second direction perpendicular to the first direction to prepare a stretched sheet. and The stretched sheet is heat-set at 110°C to 160°C to prepare a biodegradable film. The PHA resin comprises a first PHA resin containing repeating units of 3-hydroxyhexanoate (3HH) and a second PHA resin containing repeating units of 4-hydroxybutyrate (4HB).

Citation Information

Cited By

  • Seawater degradable plastic packaging barrel and preparation method thereof

    CN121537762A

  • A seawater-degradable plastic packaging barrel and a preparation method thereof

    CN121537762B